Aspirin: The Mechanism of Action Revisited in the Context of Pregnancy Complications - Cadavid, Angela P. (Frontiers in Immunology, 2017)
Aspirin is one of the most frequently used and cheapest drugs in medicine. It belongs to the nonsteroidal anti-inflammatory drugs with a wide range of pharmacological activities, including analgesic, antipyretic, and antiplatelet properties. Currently it is accepted to prescribe a low-dose of aspirin to pregnant women who are at high risk of preeclampsia because it reduces the onset of this complication. Another pregnancy alteration in which a low-dose of aspirin is recommended, is the obstetric antiphospholipid syndrome. The most recognized mechanism of action of aspirin is to inhibit the synthesis of prostaglandins but this by itself does not explain the repertoire of anti-inflammatory effects of aspirin. Later, another mechanism was described: the induction of the production of aspirin-triggered lipoxins (ATL) from arachidonic acid by acetylation of the enzyme cyclooxygenase-2. The availability of a stable analog of ATL has stimulated investigations on the use of this analog and it has been found that, similarly to endogenously-produced lipoxins, ATL resolves inflammation and acts as antioxidant and immunomodulator. If we consider that in preeclampsia and in the obstetric antiphospholipid syndrome there is an underlying inflammatory process, aspirin might be used based on the induction of ATL. The objective of this review is to revisit the old and new mechanisms of action of aspirin. In particular, it intends to show other potential uses of this drug to prevent certain pregnancy complications in the light of its ability to induce anti-inflammatory and pro-resolving lipid-derived mediators.